Model Konsep Teori Keperawatan Katherine Kolcaba - Yeni Astuty; Irna Nursanti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Katherine Kolcaba originally wrote comfort theory in Alzheimer's and dementia patients. However, Katherine herself has written several articles in the nursing field regarding her theory. When Kolcaba developed his theory, he used logical reasoning. He uses induction, deduction, subtraction. Kolcaba uses existing frameworks to synthesize or identify comfort types. This book has a provocative and profound effect, encouraging psychologists to study personality holistically and in depth and emphasizing the complex interactions between individual, social, and cultural characteristics. This is an excellent starting point for this theory because comfort is best achieved through holistic treatment. He also begins with the analytical concept of the term